2007
DOI: 10.1007/s12032-007-0010-3
|View full text |Cite
|
Sign up to set email alerts
|

Malignant mesothelioma of the tunica vaginalis testis: a case report and review of the literature

Abstract: Most often, mesotheliomas involve the serosal membranes of the pleura and peritoneum. Sometimes, mesothelial proliferations are identified in other locations. A mesothelioma, within the tunica vaginalis of the paratesticular region is rare but often fatal malignancy of the male genitalia. Despite aggressive surgical and systemic therapy the prognosis remains poor with only rare long-term survivors. We report a case of malignant mesothelioma of the tunica vaginalis in 45-years-old and review of the literature i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…In one study, 9 losses of chromosomal regions in 1p, 8p, 14q, and 22q and gains in 5p, 6p, 8q, 15q, 17q, and 20 were reported. In a separate study, chromosomal abnormalities, such as losses of 1p, 3p, 6q, 9q, and monosomy 22, were shown, 5,7 implying that mesotheliomas harbor multiple cytogenetic abnormalities with no specific diagnostic characteristics. It is not now possible to define the most important genetic alterations involved in the tumorigenesis of mesotheliomas, and future studies will be needed to delineate it at the molecular level.…”
Section: Immunohistochemistrymentioning
confidence: 95%
See 1 more Smart Citation
“…In one study, 9 losses of chromosomal regions in 1p, 8p, 14q, and 22q and gains in 5p, 6p, 8q, 15q, 17q, and 20 were reported. In a separate study, chromosomal abnormalities, such as losses of 1p, 3p, 6q, 9q, and monosomy 22, were shown, 5,7 implying that mesotheliomas harbor multiple cytogenetic abnormalities with no specific diagnostic characteristics. It is not now possible to define the most important genetic alterations involved in the tumorigenesis of mesotheliomas, and future studies will be needed to delineate it at the molecular level.…”
Section: Immunohistochemistrymentioning
confidence: 95%
“…Later, Plas et al 5 reviewed 74 cases of mesothelioma of the tunica vaginalis testis and found that 34.2% had a history of asbestos exposure. [7][8] The latency period from the initial asbestos exposure to the clinical diagnosis is variable but is usually long, sometimes as long as 40 years. 9 CLINICAL FEATURES Mesothelioma of the tunica vaginalis occurs in middleaged to elderly men (mean, 53.5 years); however, there is one case in the literature 10 that describes this entity occurring in the pediatric population.…”
mentioning
confidence: 99%
“…These findings strongly suggest that canine MM of the tunica vaginalis testis shares immunophenotypic characteristics with a similar neoplasm reported in human beings. 10 Although the outcome of MM of the tunica vaginalis testis is not known for every reported case in human beings, the overall clinical prognosis for mesothelioma is poor, 4 and, as such, radical orchiectomy should be the first-line therapy. 11 The efficacy of adjuvant chemotherapy and radiotherapy has not yet been clearly determined.…”
mentioning
confidence: 99%
“…In rare cases, mesothelioma can also occur in the pericardium (4) or in the testis tunica vaginalis (5). Here …”
Section: Malignant Mesotheliomas Are Rare But Aggressive Tumors Arisimentioning
confidence: 99%